Inspection and Training using Virtual Reality Applied a new Wheel Loader Model - Borges, Luiz F. M. R.; Miranda, Arthur S.; Ferreira, João V. L.; Lazarini, Thales Pinheiro; A. Neto, Alexandre De; Novais, Matheus G.; Martins, Thiago S.; Andreão, Rodrigo Varejão; Schimidt, Marcelo Q.; Mestria, Mário (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
This study introduces a new wheel loader model designed to enhance the inspection and training process for the handlers at a mining industry. This model incorporates advanced features, providing a comprehensive and realistic training experience. A key component is a virtual reality simulator, developed using a cross-platform game engine. This simulation serves as an interactive tool for performing maintenance inspection procedures, addressing a critical need for effective pre-operation safety instruction. The software was tested by 16 qualified professionals from the industry, across different conditions. The results demonstrated that the simulator significantly improves the initial training experience. Therefore, it allows employees to gain essential skills and knowledge without exposure to real-world risks. In addition, the new wheel loader model incorporates more real-life immersion as the interior of the cabin. It is constituted of the buttons and proper texturing, enabling operators to identify and address potential issues. Thus, further minimizing operation disruptions. Overall, the integration of this advanced wheel loader model with a sophisticated virtual reality apprenticeship not only enhances safety but also reduces machine downtime. Moreover, the integration allows reduced training costs and it provides a highly effective solution. Consequently, it ensures that operators are well-prepared for a wide range of situations that they may come across in the real world.